Comparing the effects of three local anaesthetic agents on cardiac conduction system - A randomised study - Vaishali Agarwal; Pravin K. Das; Soumya S. Nath; Manoj Tripathi; Bhuwan Tiwari (Indian Journal of Anaesthesia)
Background and Aims: This study aimed to compare the effects of three local anaesthetic (LA) agents, namely bupivacaine, levobupivacaine, and ropivacaine, on the cardiac conduction system as assessed by corrected QT (QTc) and P wave dispersion (PWD) intervals in lower limb orthopaedic surgeries and to find the most suitable LA agent that can be used for a long duration. Methods: The study included 75 patients with American Society of Anesthesiologists physical status I and II of either gender in the age group of 18–65 years undergoing elective lower limb orthopaedic surgeries under epidural anaesthesia. These were allocated to groups B (bupivacaine), L (levobupivacaine), and R (ropivacaine). We observed blood pressure, heart rate, respiratory rate, PWD, and QTc intervals from baseline value through Holter monitoring, pain assessment by visual analogue scale, and demand and total volume of LA consumed by patient-controlled analgesia devices. The repeated measures of ANOVA were carried out to find the effect of time and time-to-group interaction among the groups across the periods. Results: On intergroup comparison of QTc and PWD, no significant difference among groups was observed, but on intragroup analysis, a statistically significant increase in QTc and PWD from baseline was observed for each of groups B, L, and R at all time intervals. However, the mean increase in QTc and PWD recorded for Group B was higher than in groups L and R. Conclusions: Bupivacaine has the maximal tendency to prolong QTc and PWD. All three agents showed comparable haemodynamic effects and time to onset of sensory and motor blockade.